Editorial - Acle Tomasini, Guadalupe (2022)
The importance and interest of fostering an academic space that allows researchers and teachers to discuss the various challenges facing higher education and teachers of higher education to debate the various challenges facing university teaching and higher education is reflected in some of the articles in this issue. and higher education is reflected in some of the articles in this issue, which is precisely the result of the collaboration between the Revista Digital de Docencia Universitaria and the Mexican Network of Educational Research of the Mexican Network of Educational Research of the Mexican System of Research in Psychology.